Exploration of Symbiotic Bacteria of Oryctes rhinoceros (Coleoptera: Scarabaeidae) Larvae from Oil Palm Empty Fruit Bunches - Marheni Marheni; Edhi Martono; Octanina Sari Sijabat (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2021)
Oil palm empty fruit bunches (OPEFB) were utilized as the source of organic fertilizer, but become a medium of Oryctes rhinoceros proliferation in oil palm plantations. O. rhinoceros uses cellulose, hemicellulose and lignin in the OPEFB as energy sources for larvae growth and development. In the process of breaking and combining complex compounds into simple molecules, they are establishing symbiotic relationship with bacteria residing in the digestive tract of O. rhinoceros larvae. Isolation of the symbiotic bacteria of the O. rhinoceros larvae was carried out with the aim of identifying bacteria in the digestive tract of the third instar found in the OPEFB. This research was done by using a descriptive method. Exploration of symbiotic bacteria of O. rhinoceros larvae was conducted through two stages. The first step was attained by isolating, growing and multiplying the bacteria and conducting biochemical testing. The second phase was accomplished by molecular testing for bacterial identification. The results showed that bacterial isolates were found and and after molecularly sequenced based on 6S rDNA, the species were identified as Bacillus stratosphericus, B. siamensis, B. cereus, Haemophilus parainfluenzae, Achromobacter xylosoxidans, and Alcaligenes faecalis. The research also found several species of bacteria originating from the hindgut larvae O. rhinoceros.